Women’s empowerment, agricultural extension, and digitalization: Disentangling information and role model effects in rural Uganda - Lecoutere, Els; Spielman, David J.; Van Campenhout, Bjorn (International Food Policy Research Institute, 2019)
In many developing countries, agricultural extension services are generally biased towards men, with information targeted mainly to male members of a farming household and in formats that are rarely tailored to female members. Nevertheless, female farmers may also benefit from such services as this may affect their ability to make informed decisions, resulting in increased farm productivity, household income, and welfare. We conduct a gendered field experiment among maize-farming households in eastern Uganda to test whether video-enabled extension messaging affects outcomes related to maize cultivation. In this experiment, men, women, and couples are shown randomly assigned videos about improved maize management practices in which male, female, or both male and female actors are featured. We first vary exposure to the videos by gender to test the effects of changes in intra-household information asymmetries, investigating whether involving women as recipients of information increases their ability to participate in household decision-making, and thus their involvement in household production choices. We then vary exposure to the gender of the actors in the videos to test for role-model effects, exploring whether involving women as information messengers challenges the idea that decision-making is a predominantly male domain, in turn affecting women’s outcomes. Results show that targeting women with information increases their knowledge about improved maize management practices, their role in agricultural decision-making, the adoption of recommended practices and inputs, production-related outcomes, and the quantity of maize women sell to the market. Results for the role-model effects are mixed, and are evident more in joint household outcomes than individual women’s outcomes. Overall, our findings suggest that in the context of our study, extension efforts aimed at directly addressing intra-household information asymmetries may be a first-best means of empowering women in agriculture. Other, more subtle means that seek to influence perceptions and norms about gendered roles in the household may not generate expected effects or work via expected impact pathways, though they remain worth further exploration.